Fabrication of hydrogenated amorphous silicon-based solar cells using RF-PECVD - Prayogi, Soni; Wibowo, Wahyu Kunto (International Journal of Applied Power Engineering (IJAPE), 2025)
Thin-film solar cells made of hydrogenated amorphous silicon have succeeded in crystallization technologies as a less expensive alternative because of their straightforward design, sparse material requirements, low processing temperatures, and cheap manufacturing costs. A multi-chamber plasma-accelerated chemical vapor deposition apparatus driven by radio frequency was used to create the intrinsic and extrinsic layers of the a-Si: H solar cell. Multi-chamber allows us to upgrade each layer of the gadget utilizing a distinct space, preventing cross-contamination throughout the procedure. To enhance cell conversion efficiency, a thorough analysis has been conducted in this work to evaluate the manufacturing process and comprehend the link between process factors and property dependency. Our findings demonstrate an amorphous Si: H solar cell with a maximum cell efficiency of 6.52%, Voc 880 mV, Isc 11.33 mA/cm2, and FF 65%. We think that a modeling method followed by manufacturing can further enhance the performance of a-Si: H-based solar cell devices.